Three prognostic indexes as predictors of response to adjuvant chemoradiotherapy in patients with oral squamous cell carcinoma after radical surgery: A large‐scale prospective study. Issue 2 (15th December 2018) - Chen, Fa; Lin, Lisong; Liu, Fengqiong; Yan, Lingjun; Qiu, Yu; Wang, Jing; Hu, Zhijian; Wu, Junfeng; Bao, Xiaodan; Lin, Liangkun; Wang, Rui; Cai, Lin; et al.
Abstract: Background: To develop and validate practical prognostic indexes (PIs) for predicting the prognosis and response to postoperative adjuvant therapy in patients with oral squamous cell carcinoma (OSCC). Methods: A large cohort of 1071 OSCC patients were randomized to either training set ( N = 708) or validation set ( N = 363). Three types of PIs were developed according to the nomogram scores, β coefficients and excess hazard ratios, respectively. Restricted cubic spline was used to demonstrate the relationship between PIs and the risks of death. Results: First, a nomogram was developed incorporating age at diagnosis, smoking status, clinical stage, tumor differentiation, lymph node status, comorbidity, and neutrophil to lymphocyte ratio levels. Then, three PIs were established with high survival predictive ability, and were superior to AJCC staging system (all P < .05). The risks of death were escalated continuously with the increasing number of PIs. Interestingly, adjuvant chemoradiotherapy was positively associated with poor overall survival in patients with low PIs, but exerted a beneficial effect on patients with high PIs. Conclusion: Combined nomogram with further established PIs not only predicts the survival probability of OSCC patients, but also continuously quantifies the risk of death. High PIs could predict a beneficial response to adjuvant chemoradiotherapy, whereas low PIs indicate an unfavorable response.